Laughter Yoga and Older Adults - Turan, Gülcan Bahçecioğlu; Gür, Fatma (Nova Science Publishers, Inc., 2026)
Adding years to life is a great achievement if the older adult has independence, well-being, and good health. However, individuals’ longevity also increases the incidence of health problems and care needs that reduce functional independence and increase dependence on other individuals. This significant increase suggests what should be done to maintain a better quality of life for older adults and improve their health and independence. It can be seen that, especially in recent years, laughter therapy has been used as a nursing intervention to reduce disease-related symptoms, improve health, and increase the quality of life in older adults. Laughter yoga has been shown to have positive health and well-being benefits in older adults. Research shows that older adults who participate in regular laughter yoga sessions experience improvements in their mood, stress levels, social interactions, and overall health. A growing body of evidence shows the health benefits of laughter. These include reducing stress, increasing blood pressure and stress hormones, increasing muscle stretching, and triggering the release of endorphins, the body’s natural pain-relieving chemicals that produce an overall sense of well-being. For this reason, laughter yoga should be an integral part of the health promotion processes of caregivers of older adults. It can be an effective tool to improve the lives of older adults through its inclusion and dissemination in individual and community health programs. Copyright © 2026 by Nova Science Publishers, Inc.
Keywords: Health; Laughter Yoga; Older Adults; Well-Being